Analysis of senior school students’ preconceptions regarding the concept of climate change in terms of visual representation explorations - Yani, Sindi; Ismail, Ali; Fitria Amalia, Irma (Insitut Pendidikan Indonesia, 2023)
Preconceptions are essential initial understandings that students possess, as they serve as the foundation for better learning. Regarding the concept of climate change, many students still harbor misconceptions. One way to identify students’ preconceptions is through the use of visual representations. The use of visual representations can unveil students’ preconceptions about abstract and complex concepts. This study aims to observe and analyze the extent of high school students’ understanding of climate change. It employs qualitative descriptive research, with a population and sample comprising 63 tenth-grade students majoring in natural sciences at a high school in Indonesia. Data collection techniques involve observation and interviews, with semi-structured interviews utilized in this study. The results reveal that students have varied understandings of the climate change concept, with many still holding misconceptions. There are three categories of climate change concepts: 1) accurate climate change concepts, accounting for 37% (23 students); 2) climate change concepts based on objects, as observed from the overall visualized images created by the respondents; and 3) incorrect climate change concepts, constituting 63% (40 students). From these categories, based on empirical evidence regarding students’ preconceptions of climate change, it falls into the macroscopic level.